Current progress in research focused on salt tolerance in Vitis vinifera L. - Han, Yan; Li, Xiujie (Frontiers in Plant Science, 2024)
Soil salinization represents an increasingly serious threat to agronomic productivity throughout the world, as rising ion concentrations can interfere with the growth and development of plants, ultimately reducing crop yields and quality. A combination of factors is driving this progressive soil salinization, including natural causes, global climate change, and irrigation practices that are increasing the global saline-alkali land footprint. Salt stress damages plants both by imposing osmotic stress that reduces water availability while also inducing direct sodium-and chlorinemediated toxicity that harms plant cells. Vitis vinifera L. exhibits relatively high levels of resistance to soil salinization. However, as with other crops, grapevine growth, development, fruit yields, and fruit quality can all be adversely affected by salt stress.Many salt-tolerant grape germplasm resources have been screened in recent years, leading to the identification of many genes associated to salt stress and the characterization of the mechanistic basis for grapevine salt tolerance. These results have also been leveraged to improve grape yields through the growth of more tolerant cultivars and other appropriate cultivation measures. The present review was formulated to provide an overview of recent achievements in the field of research focused on grapevine salt tolerance from the perspectives of germplasm resource identification, the mining of functional genes, the cultivation of salt-tolerant grape varieties, and the selection of appropriate cultivation measures. Together, we hope that this systematic review will offer insight into promising approaches to enhancing grape salt tolerance in the future.